Upaya Badan Pertanahan Nasional Sebagai Pelaksana Administrasi dari Putusan Pengadilan yang Sudah Berkekuatan Hukum - Erico Cardova; Benny Djaja (UNES Law Review, 2023)
In Indonesia, a rule-of-law state, the relationship between the government and citizens is governed by Administrative Law, ensuring the effectiveness, legitimacy, and legality of state administration. The National Land Agency, established to supervise and nurture land administration, plays a crucial role in implementing the Basic Agrarian Law and managing land registration in accordance with prevailing regulations. Literature studies reveal that the National Land Agency is responsible for providing legal certainty and protecting rights, particularly regarding land ownership. This responsibility includes data management, dispute resolution, and ensuring compliance with legal provisions in court proceedings. The conclusion underscores the importance of the National Land Agency's role in upholding law and safeguarding landholder rights.